AEA Randomized Controlled Trials 2014
DOI: 10.1257/rct.536
|View full text |Cite
|
Sign up to set email alerts
|

OneStepataTime:TheEffectsofanEarlyLiteracyTextMessagingProgramforParentsofPreschoolers

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 25 publications
1
72
0
Order By: Relevance
“…Interventions that have endeavored to maintain the interest of parents by mitigating behavioral barriers that prevent greater commitment to their children have achieved better results than if they had viewed the parents merely as vehicles of information. York and Loeb (2018) evaluated a reading program, nding that children whose parents believed in the bene ts of the program obtained better results than those whose parents did not (30). Similarly, Mayer et al (2018) showed that the provision of immediate rewards to parents contributed to achieving continuity in intervention activities (31).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Interventions that have endeavored to maintain the interest of parents by mitigating behavioral barriers that prevent greater commitment to their children have achieved better results than if they had viewed the parents merely as vehicles of information. York and Loeb (2018) evaluated a reading program, nding that children whose parents believed in the bene ts of the program obtained better results than those whose parents did not (30). Similarly, Mayer et al (2018) showed that the provision of immediate rewards to parents contributed to achieving continuity in intervention activities (31).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Allington et al (2010), for example, showed that first-and second-grade children who were randomly selected to receive a dozen free books of their choice per year for 3 years outperformed children in the control group on a high-stakes literacy assessment and that the impact was even more pronounced among low-income children. Furthermore, recent experimental evidence suggests that changes in home literacy practices are associated with improvements in children's early literacy outcomes (York & Loeb, 2014).…”
Section: Early Childhood Experiences and Children's Developmentmentioning
confidence: 99%
“…To illustrate, if schools provide a newsletter that is similarly organized across grades, they can help build the habit of parental support by providing information on what children are learning and suggestions for conversations or home activities to reinforce and extend classroom learning. Text messages have also shown promise as a strategy for stimulating parent involvement (York & Loeb, 2014), and could be used similarly across the grades.…”
Section: Continuity In Parent Involvementmentioning
confidence: 99%